Environmental law and human behaviour - Ngah, Nor Syamaliah; Mohd Hussain, Azlina (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Environmental law governs rules and regulations aimed at protecting the environment, including pollution control, natural resource management, environmental impact assessments, and biodiversity conservation. It is applied by governments, businesses, and legal practitioners to address issues such as air and water quality and sustainable development. As this field continues to evolve, governments worldwide are strengthening environmental regulations to prevent degradation, enhance regulatory effectiveness, and promote sustainable practices. Such regulations also support business growth by attracting foreign investment, improving energy efficiency, and encouraging environmentally friendly investments.